Aβ oligomers trigger and accelerate Aβ seeding. (5th June 2019) - Katzmarski, Natalie; Ziegler‐Waldkirch, Stephanie; Scheffler, Nina; Witt, Christian; Abou‐Ajram, Claudia; Nuscher, Brigitte; Prinz, Marco; Haass, Christian; Meyer‐Luehmann, Melanie
Abstract: Aggregation of amyloid‐β (Aβ) that leads to the formation of plaques in Alzheimer's disease (AD) occurs through the stepwise formation of oligomers and fibrils. An earlier onset of aggregation is obtained upon intracerebral injection of Aβ‐containing brain homogenate into human APP transgenic mice that follows a prion‐like seeding mechanism. Immunoprecipitation of these brain extracts with anti‐Aβ oligomer antibodies or passive immunization of the recipient animals abrogated the observed seeding activity, although induced Aβ deposition was still evident. Here, we establish that, together with Aβ monomers, Aβ oligomers trigger the initial phase of Aβ seeding and that the depletion of oligomeric Aβ delays the aggregation process, leading to a transient reduction of seed‐induced Aβ deposits. This work extends the current knowledge about the role of Aβ oligomers beyond its cytotoxic nature by pointing to a role in the initiation of Aβ aggregation in vivo . We conclude that Aβ oligomers are important for the early initiation phase of the seeding process.